Solid oxide electrolytic cell hydrogen electrode material loaded with nanoparticles through gas phase migration method, preparation method and application

By deposition of Cu nanoparticles using high-temperature gas phase migration method on perovskite-based materials, the problems of low catalytic activity and poor stability in SOEC were solved, and efficient CO2 reduction reaction and long-term stability were achieved.

CN119465229AActive Publication Date: 2025-02-18NANJING TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411585981.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

When perovskite materials are used as hydrogen electrode materials in solid oxide electrolytic cells (SOECs), they have low catalytic activity and poor operating stability, especially at high temperatures.

Method used

Through a simple high-temperature gas phase migration method, Cu nanoparticles are deposited on perovskite-based materials, combined with in-situ dissolution strategy, and the vacancy left behind in-position dissolution is supplemented to improve catalytic activity and stability.

Benefits of technology

It significantly improves the CO2 reduction reaction activity of SOEC hydrogen electrode materials, improves electrolytic performance and stability, and maintains good performance during long-term operation without coking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465229A_ABST
    Figure CN119465229A_ABST
Patent Text Reader

Abstract

The invention relates to a solid oxide electrolytic cell (SOEC) hydrogen electrode material loaded with nanoparticles through a gas phase migration method, a preparation method and application. Cu-La0. 2Sr0. 8Ti0. 3Fe0. 7O3-delta (LSTF) is prepared on the basis of a gas phase migration method of powder sublimation at high temperature, wherein delta is the content of oxygen vacancies. Compared with other traditional physical loading modes, Cu can be obviously and uniformly dispersed in the LSTF carrier, so that exposure of active sites is promoted. A test on SOEC taking Cu-LSTF as a hydrogen electrode shows that compared with a traditional solid oxide electrolytic cell hydrogen electrode, the hydrogen electrode which can be simply prepared has excellent CO2 reducing capacity. The novel hydrogen electrode material shows excellent electrochemical performance and shows excellent stability in a long-term test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid oxide electrolytic cell hydrogen electrode material, a preparation method and a use thereof, which is loaded with nanoparticles by a simple gas phase migration method. 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ The invention discloses a preparation method and application of a composite anode, belonging to the technical field of electrode materials for solid oxide electrolytic cells. Background Art

[0003] Solid oxide electrolyzer (SOEC) is an efficient energy conversion technology that can convert electrical energy and thermal energy into chemical energy under high temperature conditions, especially showing great potential in water electrolysis and direct electrolysis of CO2. Among various electrochemical technologies, high-temperature CO2 electrolysis by SOEC has significant advantages over other technologies, such as high current density, strong stability, and Faraday efficiency close to 100%, making it more suitable for practical applications. SOEC single cell consists of a hydrogen electrode, an oxygen electrode and an electrolyte. Both the hydrogen electrode and the oxygen electrode are porous materials, which facilitates gas transport. The electrolyte is a dense material to prevent electron transfer from short-circuiting the battery. During the high-temperature electrolysis of CO2, CO2 is reduced at the hydrogen electrode to form CO and O 2- , O 2- It passes through the electrolyte to reach the anode side to form O2. Therefore, research on SOEC mainly focuses on how to improve the catalytic activity and stability of hydrogen electrode materials and reduce costs. Traditional SOEC hydrogen electrode materials usually use Ni-based metal-ceramic composite electrodes, but this material is prone to nickel metal agglomeration, carbon deposition, poisoning and other phenomena on the surface at high temperatures, resulting in performance degradation. In order to solve these problems, researchers have explored a variety of new cathode materials. Perovskite oxides have attracted attention due to their unique structure and tunable chemical properties. By adjusting the chemical composition and microstructure, the adsorption capacity and catalytic activity of CO2 can be improved, thereby improving the electrolysis performance and stability.

[0004] However, the relatively poor CO2 reduction reaction (CO2RR) activity of perovskite materials is the main problem they face, and the service life and stability of perovskite materials under high temperature conditions are also the main bottlenecks for commercialization. Therefore, the development of high-performance bifunctional hydrogen electrodes with high electrocatalytic activity and stability is of great significance for SOEC electrolysis of CO2. The interface between metal nanoparticles (NPs) and transition metal oxide supports is generally considered to be the active site for many important catalytic reactions. Maximizing the metal-oxide interface sites is an effective way to improve catalytic performance. The in situ dissolution method through reducing atmosphere treatment can provide excellent catalytic activity and form a unique nanoparticle-perovskite interface with high resistance to agglomeration. However, during the reduction process, the dissolution of B-site reducible cations inevitably leaves many B-site vacancies in the perovskite bulk phase, which is not conducive to the long-term operation of the electrolytic cell and greatly affects the stability. Therefore, new strategies are urgently needed to improve the stability of dissolved metal particles under long-term operation and promote the precipitation of nanoparticles. Summary of the invention

[0005] The problem of low catalytic activity and poor operating stability of perovskite materials as hydrogen electrode materials in the electrolysis of CO2 in SOEC is addressed. In the preparation process of hydrogen electrode materials, the present invention directly deposits powder materials onto the original perovskite-based materials through a simple high-temperature gas migration strategy, and combines an in-situ dissolution strategy to provide catalytically active nano-metal particles while supplementing the vacancies left by the dissolution of the B site, so as to improve the existing catalytic materials used in the CO2RR process in solid oxide electrolyzers. The catalytic activity is poor and the long-term high-temperature operating stability is poor. The present invention prepares hydrogen electrode materials by a method of loading nanoparticles through a gas phase migration strategy. The chemical formula of the material is Cu-La 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ (LSTF), this method improves the CO2RR activity of SOEC hydrogen electrode materials. Commercial cuprous oxide powder can sublimate at a temperature close to the melting point and deposit on the surface of LSTF material under the purge of airflow, which greatly enhances the ability of LSTF material to electrolyze CO2, making the single cell show good stability in long-term operation of 1000h without coking.

[0006] A solid oxide electrolytic cell hydrogen electrode material comprises a substrate electrode material and Cu loaded on the surface of the substrate electrode material, wherein the Cu is loaded on the surface of the substrate by gas phase migration and exists in the form of Cu metal; and the mass ratio of Cu is in the range of 0.5-5wt%.

[0007] The mass percentage of Cu is in the range of 1.5-2.5%.

[0008] The substrate electrode material is a perovskite material containing Fe at the B position.

[0009] The matrix electrode material is La 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ (LSTF).

[0010] The method for preparing the above-mentioned solid oxide electrolytic cell hydrogen electrode material comprises the following steps:

[0011] The base material and CuO are placed in an inert atmosphere with a certain distance between CuO and the base material, and heat treated so that cuprous oxide diffuses to the surface of the base material in the form of gaseous atoms at high temperature.

[0012] The distance is 1-20cm.

[0013] The heat treatment temperature is 800-1100°C, and the time is 1-5h, preferably 2.5-3.5h.

[0014] The preparation method of the matrix material comprises the following steps:

[0015] Step 1: Follow the La 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ The stoichiometric ratio of 16 H 36 O4Ti and a certain proportion of citric acid monohydrate are added to an appropriate amount of deionized water and stirred to dissolve to obtain a clear solution.

[0016] Step 2: Mix a certain proportion of La(NO3)3·6H2O and Sr(NO3) 2、 Pour Fe(NO3)3·9H2O into the solution described in step 1 and stir evenly.

[0017] Step 3: Add a certain proportion of ethylenediaminetetraacetic acid and ammonia water, adjust the pH value, continue heating and stirring until the solution becomes a viscous gel state, and then dry and calcine to obtain a powder.

[0018] The drying condition is 100-150°C for 5 hours; the calcination condition is 900-1100°C for 5-10 hours, with a heating rate of 1-10°C / min.

[0019] The pH is adjusted to 8-13.

[0020] A method for replenishing B-site metal dissolution vacancies in a perovskite material used as a hydrogen electrode material during the electrolysis of CO2 by SOEC, comprising the following steps:

[0021] The base material and CuO are placed in an inert atmosphere with a certain distance between CuO and the base material, and heat treated so that cuprous oxide diffuses to the surface of the base material in the form of gaseous atoms at high temperature;

[0022] The material is then subjected to reduction treatment.

[0023] The invention discloses a solid oxide electrolysis cell hydrogen electrode material for use in high temperature electrolysis of CO2 to generate CO in a solid oxide electrolysis cell.

[0024] The solid oxide electrolysis cell structure is hydrogen electrode | barrier layer | electrolyte | oxygen electrode, which is used for high-temperature electrolysis of CO2 to generate CO; the hydrogen electrode is made of Cu-La 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ The composite electrode is composed of La 0.4 Ce 0.6 O 2-δ (LDC), oxygen electrode uses PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 6-δ (PBSCF) material; the electrolyte uses La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ (LSGM) powder.

[0025] Beneficial Effects

[0026] The Cu-La loaded nanoparticles of the present invention 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ The solid oxide electrolytic cell hydrogen electrode material is prepared by the gas phase migration method and has the following effects:

[0027] (1) The elements in the material are evenly distributed, the synthesis method is simple and efficient, and the preparation process is simple.

[0028] (2) When LSGM is used as the electrolyte, LDC as the barrier layer, and PBSCF as the oxygen electrode, the resulting full cell has a higher current density.

[0029] (3) The in-situ dissolution method will inevitably leave B-site vacancies while improving the electrolytic activity, affecting the structural stability. Cu that migrates through the gas phase can be captured by LSTF with oxygen vacancies and has no effect on the original phase structure. Cu nanoparticles can not only provide active sites, greatly enhancing the CO2RR activity of LSTF hydrogen electrode in SOEC; during the reduction process, some of them will enter the perovskite phase, replenish the vacancies left by the dissolution of B-site Fe, and control the phase evolution of the perovskite substrate. Compared with the conventional doping and dissolution strategy, the lower metal loading can bring about higher reduction activity, lower impedance and other improvements in electrochemical activity.

[0030] (4) Cu-LSTF is an excellent hydrogen electrode material. The prepared full cell can be directly used for the electrolysis of CO2 to produce CO. The obtained full cell has a high electrolysis current density. The current density corresponding to 1.5V at 800℃ can reach 2.28Acm -2 It is better than a single cell with LSTF as the hydrogen electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the principle of preparing electrodes by vapor phase migration;

[0032] Figure 2 is the XRD pattern of Cu-LSTF-3 and LSTF hydrogen electrode materials at room temperature;

[0033] Figure 3 It is the XRD pattern of Cu-LSTF-x, hydrogen electrode material at room temperature with different deposition times;

[0034] Figure 4 This is the XRD pattern of Cu-LSTF-3 in situ reduced at high temperature in 10% H2 / Ar atmosphere;

[0035] Figure 5 is the XRD pattern of Cu-LSTF-x treated in 10% H2 / Ar atmosphere for 2 h;

[0036] Figure 6 are the morphology SEM images of LSTF and Cu-LSTF-x powders before and after reduction;

[0037] Figure 7 This is the EDX-mapping picture of Cu-LSTF-3 morphology;

[0038] Figure 8 This is the SEM and EDX-mapping picture after the Cu-LSTF electrode on the surface of the electrolyte sheet was ground off;

[0039] Fig. 9It is the HADDF-TEM and corresponding EDX-mapping images of the reduced Cu-LSTF-3;

[0040] Fig.10 are the IV and IP curves of the LSTF|LDC|LSGM|PBSCF single cell in fuel cell mode at 750-850°C;

[0041] Fig.11 are the IV and IP curves of the Cu-LSTF-3|LDC|LSGM|PBSCF single cell in the fuel cell mode at 750-850°C;

[0042] Fig.12 Electrochemical impedance spectroscopy of LSTF|LDC|LSGM|PBSCF and Cu-LSTF-3|LDC|LSGM|PBSCF single cells tested at open circuit voltage in the range of 750-850℃

[0043] Fig.13 It is the performance curve of LSTF|LDC|LSGM|PBSCF single cell electrolyzing CO2 in the temperature range of 700-850℃;

[0044] Fig.14 This is the performance curve of Cu-LSTF-1|LDC|LSGM|PBSCF single cell for CO2 electrolysis at 700-850℃;

[0045] Fig.15 This is the performance curve of Cu-LSTF-3|LDC|LSGM|PBSCF single cell for CO2 electrolysis at 700-850℃;

[0046] Fig.16 This is the performance curve of Cu-LSTF-5|LDC|LSGM|PBSCF single cell for CO2 electrolysis at 700-850℃;

[0047] Fig.17 This is a comparison chart of the electrolytic performance of LSTF and Cu-LSTF-x at 800°C;

[0048] Fig.18 Cu-LSTF-3|LDC|LSGM|PBSCF single cell at -0.8A cm -2 Long-term stability test of pure CO2 electrolysis at 800°C under constant current density;

[0049] Fig.19 It is the Raman test after the stability test of Cu-LSTF-3|LDC|LSGM|PBSCF single cell; DETAILED DESCRIPTION

[0050] The present invention relates to a solid oxide electrolytic cell (SOEC) hydrogen electrode material loaded with nanoparticles by a vapor phase migration method, a preparation method and a use thereof. Cu-La 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ (LSTF), where δ is the content of oxygen vacancies. Compared with other traditional physical loading methods, it can significantly make Cu atoms evenly dispersed in the LSTF carrier to promote the exposure of active sites. The migrated Cu atoms can not only provide active sites, but also greatly enhance the CO2RR activity of the LSTF hydrogen electrode in SOEC. At the same time, during the reduction process, part of the Cu element will enter the perovskite phase, supplement the vacancies left by the dissolution of Fe at the B site, and control the phase evolution of the perovskite substrate. SOEC with Cu-LSTF as the hydrogen electrode was tested and found that this easily prepared hydrogen electrode has excellent CO2 reduction ability compared with traditional solid oxide fuel electrodes. The new hydrogen electrode material exhibits excellent electrochemical properties and shows excellent stability in long-term tests.

[0051] When the oxygen ion conductor electrolyte LSGM and PBSCF were used as oxygen electrodes, the corresponding single cell electrolyzed CO2 at 800℃ in solid oxide electrolysis cell mode and obtained -2.28Acm at 1.5V. -2 In solid oxide fuel cell mode, the cell can achieve a maximum current density of 1.27 W cm -2 The maximum output power is 2.5W. It maintains good stability in the 1000h long-term electrolysis test without coking. The present invention develops a method for preparing a hydrogen electrode material for a solid oxide electrolytic cell loaded with nanoparticles by a gas phase migration method, which greatly improves the electrochemical performance of solid oxide fuel cells and electrolytic cells.

[0052] The electrolyte and cathode materials involved in the present invention include but are not limited to the materials in the following examples, and the optimization methods and preparation methods involved include but are not limited to the methods in the following examples. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the invention shall be included in the protection scope of the present invention.

[0053] Example 1

[0054] This embodiment provides a solid oxide electrolytic cell hydrogen electrode material Cu-La loaded with nanoparticles by a gas phase migration method. 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ The preparation method comprises the following specific steps:

[0055] (1) Weigh 4.0838 g of tetrabutyl titanate and 33.6224 g of citric acid monohydrate and add an appropriate amount of deionized water to dissolve, then add 3.4640 g of lanthanum nitrate hexahydrate, 6.7722 g of strontium nitrate, and 11.312 g of ferric nitrate nonahydrate and stir to dissolve. Weigh 23.3792 g of ethylenediaminetetraacetic acid as a complexing agent according to a molar ratio of ethylenediaminetetraacetic acid: citric acid monohydrate: metal ion = 1:2:1 and add an appropriate amount of deionized water.

[0056] (2) adding the obtained complexing agent to the dissolved metal ion solution, and then adding an appropriate amount of ammonia water to adjust the pH range of the solution to 8-13, and then heating and stirring until the water evaporates to obtain a colloidal substance.

[0057] (3) The colloidal substance is placed in an oven at 150° C. to remove moisture to obtain a precursor.

[0058] (4) The obtained precursor is placed in a high-temperature furnace at 1100°C and calcined for 10 hours to obtain the powder of LSTF electrode.

[0059] (5) The obtained LSTF powder was placed at one end of a porcelain boat, and an appropriate amount of commercial cuprous oxide powder was added to the other end. The boat was placed in a tube furnace and treated in an Ar gas atmosphere at 1000 °C for 3 h to obtain the final powder.

[0060] Example 2

[0061] This embodiment provides a Cu-La 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ The preparation and testing method of a single cell for a hydrogen electrode is as follows:

[0062] (1) Weigh 1 g of the electrode powder La prepared in Example 1. 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ In a high-energy ball ink tank, add 10 mL of isopropanol, 2 mL of ethylene glycol, and 0.8 mL of propylene glycol, and mill at 400 r / min for 30 min to obtain the desired electrode slurry.

[0063] (2) Place the prepared LSGM electrolyte sheet with the LDC barrier layer sprayed on one side on a heating table at 150°C, and spray the prepared LSTF electrode slurry evenly on the surface of the LDC side using an inert gas and a spray gun. After the liquid is completely evaporated, place the sprayed electrolyte sheet in a high-temperature furnace at 1000°C and calcine for 2 hours to obtain the desired single cell. After cooling, spray PBSCF on the other side of the LSGM electrolyte, place the battery on one side of the porcelain boat, add an appropriate amount of commercial cuprous oxide powder, place it in a tubular furnace, and treat it in an Ar gas atmosphere at 1000°C for 3 hours to obtain the final single cell. The peak power density of the battery measured in the fuel cell mode at 800°C is 1.27W cm -2 , and the current density obtained in the electrolytic cell mode was -2.28Acm -2 (1.5V).

[0064] Comparative Example 1

[0065] This comparative example is used to prepare La oxide 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ (LSTF), the specific steps are as follows:

[0066] (1) Weigh 4.0838 g of tetrabutyl titanate and 33.6224 g of citric acid monohydrate and add an appropriate amount of deionized water to dissolve, then add 3.4640 g of lanthanum nitrate hexahydrate, 6.7722 g of strontium nitrate, and 11.312 g of ferric nitrate nonahydrate and stir to dissolve. Weigh 23.3792 g of ethylenediaminetetraacetic acid as a complexing agent according to a molar ratio of ethylenediaminetetraacetic acid: citric acid monohydrate: metal ion = 1:2:1 and add an appropriate amount of deionized water.

[0067] (2) adding the obtained complexing agent to the dissolved metal ion solution, and then adding an appropriate amount of ammonia water to adjust the pH range of the solution to 8-13, and then heating and stirring until the water evaporates to obtain a colloidal substance.

[0068] (3) The colloidal substance is placed in an oven at 150° C. to remove moisture to obtain a precursor.

[0069] (4) The obtained precursor is placed in a high-temperature furnace at 1100°C and calcined for 10 hours to finally obtain the electrode powder.

[0070] Comparative Examples 2 and 3

[0071] The Cu-La prepared in Example 1 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δFor powder, the processing time was changed from 3 h in Example 1 to 1.5 h.

[0072] Test Results

[0073] 1. X-ray diffraction (XRD) characterization

[0074] Figure 1 This is a schematic diagram of the principle of preparing electrodes by vapor phase migration. Cu can be loaded on LSTF through this simple method. Figure 2 The XRD patterns of Cu-LSTF-3 and LSTF hydrogen electrode materials at room temperature are shown in the XRD patterns. The XRD patterns clearly show that the LSTF powder sintered at 1100℃ in air for 10h has a cubic perovskite La 0.2 Sr 0.8 TiO3 structure. Cuprous oxide diffuses in the form of gaseous atoms along the argon gas flow at high temperatures and can be captured by LSTF. Cu-LSTF-3 also reacts with La 0.2 Sr 0.8 The standard peak of TiO3 is completely consistent, but the characteristic peak of metal Cu does not appear, probably due to the small migration amount.

[0075] Figure 3 The XRD patterns of Cu-LSTF-x at room temperature are shown in Figure 2, where x is the treatment time, which is 0, 1, 3, and 5 hours. The XRD patterns of Cu-LSTF-x powders at different treatment times clearly show that they also have a cubic perovskite structure, which is similar to La 0.2 Sr 0.8 The characteristic peaks of TiO3 remain consistent, and no additional peaks appear. And as the treatment time increases, the main diffraction peak moves to a lower diffraction angle.

[0076] Figure 4 This is the in-situ XRD spectrum of Cu-LSTF-3 material in 10% H2 / Ar atmosphere, from room temperature to 800°C. According to Figure (b), it can be seen that in the reducing atmosphere, as the temperature increases, characteristic peaks of Cu element appear at 43.3° and 50.4°. It is confirmed that the Cu in LSTF after treatment exists in a metallic state.

[0077] Figure 5 This is the XRD spectrum of Cu-LSTF-x treated in 10% H2 / Ar atmosphere for 2h. It can be found that after reduction, the formation of RP phase can be clearly seen, and the characteristic peaks of Cu and Fe elements on the perovskite surface appear.

[0078] 2. Scanning Electron Microscope (SEM) Characterization

[0079] Figure 6The SEM images of the morphology of LSTF and Cu-LSTF-x powders before and after reduction show that the morphology of LSTF and Cu-LSTF powders before reduction is basically the same, both with smooth surfaces, while the Fe nanoparticles precipitated from LSTF after reduction are larger in size, while the density of Cu-LSTF precipitated particles is significantly increased and the particle size is also significantly reduced. This indicates that the migration of Cu is conducive to improving the precipitation of Fe elements in LSTF and increasing active sites.

[0080] Figure 7 This is the EDX-mapping picture corresponding to Cu-LSTF-3, which shows the uniformity of the overall distribution of La, Sr, Ti, Fe, Cu and O elements. The atomic ratios shown in the spectrum are close to the stoichiometric ratio, and the Cu content is about 2wt%.

[0081] Figure 8 These are the SEM and EDX-mapping images after the Cu-LSTF electrode on the surface of the electrolyte sheet was ground off. Cu still exists after removing the surface LSTF, proving that Cu not only migrates to the electrode surface, but diffuses into the entire electrode.

[0082] 3. High-angle annular dark-field transmission electron microscopy (HADDF-TEM) characterization

[0083] Fig. 9 The HADDF-TEM and corresponding EDX-mapping images of reduced Cu-LSTF-3 are shown in Figure 2. The Cu-LSTF-3-R oxide was studied by high-resolution TEM, and its lattice spacing is with La 0.2 Sr 0.8 The (110) lattice plane of TiO3 corresponds to the lattice spacing of the uniform nanoparticles on the surface. EDX-mapping shows the uniformity of the overall distribution of La, Sr, Ti, Fe, Cu and O elements, and after reduction, the Cu element evenly enters the LSTF bulk phase, filling the B-site vacancy caused by Fe dissolution.

[0084] 4. Fuel cell performance test

[0085] Assembly and testing of single cell: The single cell structure is LSTF|LDC|LSGM|PBSCF (active area 0.45cm 2 ). Apply silver glue to both sides of the prepared single cell electrodes, connect them with silver wires, and seal them on a ceramic tube with a diameter of 12 mm using silver paste. The oxygen electrode side is directly exposed to the air. Before the test, 70 ml min is passed into the hydrogen electrode side. -1H2, heated to the test temperature. Under open circuit voltage, a current step of 30 mA was applied to the single cell, and the IV value of the cell was collected using a Keithley 2420 digital source meter.

[0086] Fig.10 and Fig.11 The IV and IP curves of LSTF|LDC|LSGM|PBSCF and Cu-LSTF-3|LDC|LSGM|PBSCF single cells in fuel cell mode within 850-750℃; the peak power densities of Cu-LSTF-3 electrode at 850, 800 and 750℃ are 1.60, 1.27 and 0.89 W cm, respectively. -2 The peak power of LSTF electrode at 800°C is only 0.8 W cm -2 .

[0087] Fig.12 The electrochemical impedance spectra of (a) single cell LSTF|LDC|LSGM|PBSCF and (b) single cell Cu-LSTF-3|LDC|LSGM|PBSCF tested at open circuit voltage in the range of 750-850℃. From the test results, it can be seen that the polarization impedance is 0.15Ωcm at 850℃. 2 Around, the polarization impedance is 0.15Ωcm at 800℃ 2 Around, the polarization impedance is 0.21Ωcm at 750℃ 2 The polarization impedance of LSTF at 850, 800 and 750℃ is 0.22, 0.28 and 0.40Ωcm respectively. 2 .

[0088] 5. Electrolytic cell performance test

[0089] The assembly of the electrolytic cell is the same as that of the fuel cell. The test conditions are changed to: before the test, 70 ml min is passed to the hydrogen electrode side. -1 H2, heat to test temperature, reduce for 20 min, then switch to 40 ml min -1 CO2. Under open circuit voltage, a current step of -10 mA was applied to the single cell, and the IV value of the cell was acquired using a Keithley 2420 digital source meter.

[0090] Fig.13 and Fig.14 , 151 and 16 are the IV curves of LSTF|LDC|LSGM|PBSCF and single cells Cu-LSTF-1|LDC|LSGM|PBSCF, Cu-LSTF-3|LDC|LSGM|PBSCF, and Cu-LSTF-5|LDC|LSGM|PBSCF in electrolytic cell mode at 700-850°C, respectively. The current densities of the Cu-LSTF-3 single cell under pure CO2 conditions at 1.5V are -3.3, -2.28, -1.49, and -0.91 A cm, respectively. -2 The current density of the LSTF single cell under the test conditions of 800℃ and 1.5V is only -1.36A cm -2 .

[0091] Fig.17 This is a comparison of the electrolytic performance of LSTF, Cu-LSTF-1, Cu-LSTF-3 and Cu-LSTF-5 at 700-850°C. At 800°C and 1.5V, the corresponding current densities are -1.36, -1.60, -2.28 and -2.03 A cm -2 . This indicates that the Cu-LSTF-3 electrode has excellent CO2RR activity.

[0092] 12. Single battery durability test

[0093] Fig.18 At 800℃, the Cu-LSTF-3 electrode is -800mA cm -2 Constant current density pure CO2 electrolysis stability test. During the 1000h test, the voltage of the electrolytic cell was stable at 1.5V with no obvious degradation, indicating good long-term stability of the electrolytic cell.

[0094] Fig.19 After long-term stability testing of the Cu-LSTF-3|LDC|LSGM|PBSCF single cell in a pure CO2 atmosphere at 800°C, no obvious carbon deposition was observed on the Cu-LSTF-3 hydrogen electrode after Raman testing.

Claims

1. A solid oxide electrolytic cell hydrogen electrode material, characterized in that: It includes a substrate electrode material and Cu loaded on the surface of the substrate electrode material, wherein Cu is loaded on the surface of the substrate by gas phase migration and exists in the form of Cu metal; and The mass ratio of Cu is in the range of 0.5-5wt%.

2. The solid oxide electrolytic cell hydrogen electrode material according to claim 1, characterized in that: The mass percentage of Cu is in the range of 1.5-2.5%.

3. The solid oxide electrolytic cell hydrogen electrode material according to claim 1, characterized in that: The substrate electrode material is a perovskite material containing Fe at the B position.

4. The solid oxide electrolytic cell hydrogen electrode material according to claim 1, characterized in that: The matrix electrode material is La 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ (LSTF).

5. The method for preparing the solid oxide electrolytic cell hydrogen electrode material according to claim 1, characterized in that: The steps include: The base material and CuO are placed in an inert atmosphere with a certain distance between CuO and the base material, and heat treated so that cuprous oxide diffuses to the surface of the base material in the form of gaseous atoms at high temperature.

6. The method for preparing a solid oxide electrolytic cell hydrogen electrode material according to claim 5, characterized in that: The distance is 1-20cm.

7. The method for preparing a hydrogen electrode material for a solid oxide electrolytic cell according to claim 5, characterized in that: The heat treatment temperature is 800-1100°C, and the time is 1-5h, preferably 2.5-3.5h.

8. The method for preparing a solid oxide electrolytic cell hydrogen electrode material according to claim 5, characterized in that: Step 1: Follow the La 0.2 Sr 0.8 Ti 0.3 Fe 0.7 O 3-δ The stoichiometric ratio of 16 H 36 O4Ti and a certain proportion of citric acid monohydrate are added to an appropriate amount of deionized water and stirred to dissolve to obtain a clear solution; Step 2: Add a certain proportion of La(NO3)3·6H2O, Sr(NO3) 2、 Pour Fe(NO3)3·9H2O into the solution described in step 1 and stir evenly.

9. A method for replenishing B-site metal dissolution vacancies in a perovskite material used as a hydrogen electrode material for electrolysis of CO2 in a SOEC, comprising the following steps: heat-treating a base material and CuO in an inert atmosphere with a certain distance between CuO and the base material, so that cuprous oxide diffuses to the surface of the base material in the form of gaseous atoms at high temperature; and then reducing the material.

10. Use of the solid oxide electrolytic cell hydrogen electrode material according to claim 1 in high-temperature electrolysis of CO2 to produce CO in a solid oxide electrolytic cell.

Citation Information

Patent Citations

  • Oxide with perovskite-type structure, preparation methods and applications

    CN103427094A

  • Solid oxide electrolytic cell hydrogen electrode material and preparation method and application thereof

    CN116477666A

  • Metal nanoparticle modified R-P perovskite solid oxide electrolytic cell cathode material as well as preparation method and application thereof

    CN117344317A

  • Surface-enhanced Raman substrate and preparation method thereof

    CN117776256A

  • Cathode material for solid oxide electrolytic cell, and preparation method therefor and use thereof

    WO2024094093A1